Fecundity of the shrimp Macrobrachium jelskii (Miers, 1877) in the southern portion of the state of Ceará, Brazil - Nery, Mariane Fernandes Gomes; Pinheiro, Allysson Pontes; Silva, Daniele Sobreira; Duarte, Antonia Rosivania Rodrigues; Lucena, Isis Campos de (Scientia Plena, 2015)
Biological knowledge on freshwater shrimps of the genus Macrobrachium is of the utmost importance due to the fundamental ecological role these organisms play in aquatic ecosystems. Few studies have been carried out on the biology and ecological relations of Macrobrachium jelskii in the semiarid regions of northeastern Brazil. The aim of the present study was to evaluate the fecundity of populations of the shrimp M. jelskii from rivers in different locations in the state of Ceará, Brazil. Sampling was carried out between June 2012 and February 2013 in the municipalities of Juazeiro do Norte, Lavras da Mangabeira, Milagres, Várzea Alegre and Farias Brito. Seventy-three ovigerous females were caught, with the cephalothorax length ranging from 6.62 mm to 10.98 mm. The largest mean fecundity rates were found in the municipalities of Milagres and Várzea Alegre. The increase in the number of eggs was associated with an increase in carapace length.